Planar cell polarity proteins determine basal cell height in the later stage embryonic mouse epidermis' [version 2; peer review: 2 approved] - Carl Hobbs; Caroline J. Formstone (Wellcome Open Research, 2023)
Background: Complex organ formation requires the coordinated morphogenesis of adjacent tissue layers. Here, we report a role for the planar cell polarity (PCP) proteins Fz6 and Celsr1 in generating squamous basal cells in the later stage embryonic epidermis of the mouse is reported, which may impact upon the shape of overlying suprabasal cells. Methods: The depth of the epidermis and basal layer as well as cell proliferation index was scored from immunostained wax sections taken from different mouse embryos mutant in planar cell polarity signalling and their wild-type littermates. Orientation of epidermal cell division in Celsr1 Crash/Crash mutants was determined from thick frozen immunostained sections. Immunostained wax sections of wild-type skin explants cultured using the Lumox method enabled any changes in epidermal and basal layer depth to be measured following the release of surface tension upon dissection of skin away from the whole embryo.   Results: Increased numbers of columnar and cuboidal basal epidermal cells were observed in fz6-/- mutant and Celsr1 mouse mutant Crash/Crash which correlated with visibly more rounded suprabasal cells and a thicker epidermis. Conclusions: Altogether these data support tissue intrinsic roles for PCP proteins in ‘outside-in’ (radial) skin architecture.